Heterogeneous reactions in a HFCVD reactor: simulation using a 2D model - Xochitl Aleyda Morán Martínez; José Alberto Luna López; Zaira Jocelyn Hernández Simón; Gabriel Omar Mendoza Conde; José Álvaro David Hernández de Luz; Godofredo García Salgado (Beilstein Journal of Nanotechnology)
In this study, a simulation of the elementary chemical reactions during SiOx film growth in a hot filament chemical vapor deposition (HFCVD) reactor was carried out using a 2D model. For the 2D simulation, the continuity, momentum, heat, and diffusion equations were solved numerically by the software COMSOL Multiphysics based on the finite element method. The model allowed for the simulation of the key parameters of the HFCVD reactor. Also, a thermochemical study of the heterogeneous reaction between the precursors quartz and hydrogen was carried out. The obtained equilibrium constants (Keq) were related to the temperature profile in the deposition zone and used in the proposed simulation. The validation of the model was carried out by measuring the temperature experimentally, where the temperature range on the substrate is 450 to 500 °C for different deposition parameters. In the simulation, the laminar flow of species contributing to the film growth was confirmed, and the simulated concentration profiles of H° and SiO near the filaments and the sources were as expected. H° and SiO are essential species for the subsequent growth of the SiOx films. These SiOx films have interesting properties and embedded nanostructures, which make them excellent dielectric, optoelectronic, and electroacoustic materials for the fabrication of devices compatible with silicon-based technology.